(untitled) (Plant Tissue Culture and Biotechnology, 2020)
This study was aimed to investigate salt tolerance of two grapevine cultivars, ‘Chenine Blanc’ and ‘Canonannon’ through in vitro propagation on medium containing different concentrations of NaCl. Single-node shoots were cultured on MS with 1.0 mg/l BAP in combination with 0.1 mg/l IBA and containing 0.25, 0.50, 0.75, 1.00 or 1.50% NaCl. NaCl free medium was used as control. Shoots of both cultivars were cultured on the same MS containing 0.25, 0.50, 0.75 or 1.00% CaCl2 to reduce hyperhydricity. The shoots were transferred to rooting medium followed by acclimatization in greenhouse. Number and length of shoots and roots, number of leaves and nodes, length of nodes, fresh and dry weight of roots and shoots decreased significantly in consistent trend as the concentration of NaCl increased. ‘Canonannon’ cultivar was found to be significantly more tolerant to NaCl than ‘Chenine Blanc’ in all parameters. The lowest percentage of hyperhydric shoots were obtained on medium containing 0.25% CaCl2. Therefore, ‘Canonannon’ cultivar can be planted in relatively saline soils as it is more tolerant to salt than ‘Chenine Blanc’. Plant Tissue Cult. & Biotech. 30(1): 47-56, 2020 (June)